(untitled) (Revista de História da UEG (REVHIST), 2021)
The Colombian writer Gabriel Garcia Marquez (1927-2014), known for works that became bestsellers, such as One Hundred Years of Solitude (1967), also had his career and work accompanied by the professional journalism and political activity. This paper analyzes one of the Marquez’s work, first written in the 50’s, in a report format, and republished as a book in 1970, accompanied by a preface, entitled The Story of a Shipwrecked Sailor. The objectives of this paper are: a) to think about the approaches and possibilities between different narratives - historical and journalistic; b) analyze how the author, in a “non-academic modality”, constructs the content in written form; and seeks to communicate the experience of the character; and, c) reflect on the journalistic report, in the light of the debates opened by the fields of public and oral history, in relation to the possibilities of appropriation of the past undertaken by this narrative genre. Keywords: The Story of a Shipwrecked Sailor. Public history. Oral history.